Pulmonary Papillomatosis: a Rare Case of Recurrent Respiratory Papillomatosis Presenting with Multiple Nodular and Cavitary Lesions - Diah Martina; Andree Kurniawan; Ceva W Pitoyo (Acta Medica Indonesiana)
Pulmonary papillomatosis is an extremely rare variant of recurrent respiratory papillomatosis which is hard to treat, causes prolonged morbidity, and may transform into malignant disorder in several cases. Since the symptoms and radiologic findings are not specific, pulmonary papillomatosis is often being misdiagnosed. Although considered benign, pulmonary papillomatosis carries the most significant mortality. This is a case report of a 26 year old man who complained recurrent chronic cough, slight hemoptoe, occasional pleuritic pain, and several episodes of fever. He also had laryngeal papillomatosis and undergone serial endoscopic resection since his childhood. Multiple nodular and cavitary lesions, some with air fluid level, were found in both lung fields at chest radiography and scintigraphy. Diagnosis of pulmonary papillomatosis complicated with secondary infection was made after endoscopic and histologic study.